FUNDAMENTAL PRINCIPLES OF THE LEGISLATION PROCESS - Yassar Aulia; Ali Abdurahman; Mei Susanto (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2021)
The Indonesian legislative process in recent years has been facing various serious procedural flaws. Most notably illustrated by at least three contemporary cases, namely regarding the process of the second amendment to Law No. 30 of 2002 concerning the Corruption Eradication Commission (hereinafter referred to as the KPK Law); the third amendment to Law No. 24 of 2003 concerning the Constitutional Court (MK Law); and the formation of Law No. 11 of 2020 concerning Job Creation (Job Creation Law). The purpose of this paper is to see whether in practice, the legislative process in Indonesia has aligned itself with the fundamental principles of the legislative process and to see whether the legal framework regarding procedures during the law-making process are adequate. Through descriptive analytical research and comparative approach with the United Kingdom, this paper found that the Indonesian law-making process in practice is not in line with the fundamental principles of the legislative process. We also found that the legal framework regarding the procedure for making laws in Indonesia to be inadequate and therefore we suggest that it can draw some lessons from the practices of the British Parliament. Abstrak: Pembentukan undang-undang (UU) di Indonesia dalam beberapa tahun terakhir memiliki berbagai kecacatan prosedural yang serius. Kekacauan proses legislasi di Indonesia paling terang terilustrasikan jika melihat setidaknya tiga kasus kontemporer, yakni mengenai proses pembentukan UU No. 19 Tahun 2019 tentang Perubahan Kedua atas UU No. 30 Tahun 2002 tentang Komisi Pemberantasan Tindak Pidana Korupsi (selanjutnya disebut UU KPK), UU No. 7 Tahun 2020 tentang Perubahan Ketiga atas UU No. 24 Tahun 2003 tentang Mahkamah Konstitusi (UU MK), dan UU No. 11 Tahun 2020 tentang Cipta Kerja (UU Cipta Kerja). Tujuan dari tulisan ini adalah untuk melihat apakah dalam praktik, proses pembentukan UU di Indonesia telah menyelaraskan diri dengan prinsip-prinsip fundamental proses pembentukan undang-undang dan melihat apakah pranata hukum prosedural yang berlaku telah memadai. Melalui spesifikasi penelitian deskriptif analitis dan pendekatan perbandingan hukum dengan Britania Raya, hasil penelitian menunjukkan bahwa praktik pembentukan undang-undang di Indonesia belum selaras dengan prinsip-prinsip fundamental proses pembentukan undang-undang. Pranata hukum mengenai prosedur pembentukan UU yang ada di Indonesia juga kami temukan belum memadai dan oleh karenanya dapat mengambil beberapa pelajaran dari praktik Parlemen Britania Raya. Kata Kunci: Fast-Track Legislation, Omnibus Law, Pembentukan Undang-Undang, Perbandingan Hukum, Prinsip Prosedural